Analisis Kebijakan Dividen, Keputusan Investasi, dan Profitabilitas pada Perusahaan Properti, dan Real Estate yang Terdaftar di Bursa Efek Indonesia - Achmad Khanif Ismail; Dewi Ayu Wulandari (Universitas Batanghari Jambi, 2023)
This study aims to determine and analyze the effect of dividend policy, investment decisions, and profitability on the firm value in property and real estate sector. The good prospects in this sector can be seen from the increasing attractiveness of residential houses due to the increasing population of Indonesia. This study is a quantitative research using secondary data got from annual report of listing companies from Indonesia Stock Exchange (IDX). The population is the listed company in property and real estate sector period 2012-2021. By using purposive sampling, companies fulfilling the criteria in this research is 10 companies. The technique of analyzing the data is multiple regression analysis. The Result shows that dividend policy have no significant effect on firm value, meanwhile Investment decisions and profitability have positive and significant effect on firm value.